Experimental investigation on the development of wear in grouted connections for offshore wind turbine generators. (15th April 2016) - Dallyn, Paul; El-Hamalawi, Ashraf; Palmeri, Alessandro; Knight, Robert
Highlights: Wear of plain grouted connections for offshore applications have been investigated. Experiments have been designed to be representative of actual operation conditions. Influence of surface finish on wear rate is small compared to the presence of water. Wet connections show wear rates up to 18 times larger than in dry connections. Wet coefficient of friction is lower than the recommended evaluation values. Abstract: Relative displacements between grout and steel have been observed in grouted connections used for offshore wind turbine substructures, which appear to be linked to the unexpected settlements that have occurred in some offshore wind farms. A literature review has highlighted a lack of understanding of the implications that this relative movement has on the grout wear. Experimentation has therefore been undertaken to determine the influence of various factors on the wear development, including compressive stress, displacement amplitude, surface roughness and the presence of water, looking at conditions typically experienced by offshore grouted connections. These experiments have indicated that wear of the steel and grout surfaces occur, even at low magnitude compressive stresses. The presence of water has the most significant impact on wear rate, being up to 18 times higher than for the equivalent dry condition. The presence of water can also significantly reduce the coefficient of friction to values lower than typically recommended for evaluation of grouted connections. These findings demonstrate that wear of the grouted connection is likely to occur over the life of this type of offshore structures and should therefore be considered when evaluating their integrity and assessing their behaviour.